Spiritual Leadership And Autonomous Motivation On Teachers' Innovative Work Behavior - Jamaluddin Dahlan; Asrul Jabani; Fauzih; Syahrir (PT PUSTAKA CENDEKIA GROUP, 2025)
This study aims to analyze the relationship between Spiritual Leadership, Autonomous Motivation, and Innovative Behavior of Teachers in schools. The research sample consisted of 150 teachers in Kendari City with diverse demographic characteristics based on gender, age, education level, working period, and marital status. The majority of respondents are female teachers who are in the middle career stage with adequate academic qualifications and sufficient professional experience, making it relevant to examine the influence of leadership and motivation on learning innovation. Data analysis was carried out using Structural Equation Modeling. The results of the study showed that all relationships between variables were positive and significant. Autonomous Motivation has a strong influence on Teachers' Innovative Behaviors, which affirms that intrinsic motivation plays an important role in encouraging the creation and implementation of new ideas in learning. Spiritual Leadership has a strong influence on Autonomous Motivation and has a direct influence on Innovative Behavior. These findings suggest that value-based leadership is able to strengthen teachers' internal motivation, which ultimately increases their innovation capacity. This research confirms the importance of developing spiritual leadership and strengthening intrinsic motivation to encourage sustainable educational innovation.